Application of Loose Part Media to Improve Numeracy Development of Children Aged 5-6 Years - Saputri, Istika Indah; Arismunandar, Arismunandar; Herman, Herman; Mustafa, Mustafa (Journal of Education Method and Learning Strategy, 2025)
The lack of motivation of children to learn numeracy is due to the tools used in delivering material that are not interesting, teachers always use worksheets, the methods used by teachers are less varied, teachers' creativity in utilizing the materials around them is still lacking so that children feel bored and tend to play alone without paying attention to the material presented by the teacher. Therefore, researchers will use loosepart media to improve children's numeracy development. This study uses a qualitative method with a descriptive approach that aims to determine the level of numeracy development through loose part media in children aged 5-6 years in kindergarten. The subjects of this study are teachers and students of class B6 and the informants of this research are principals and teachers. Data collection techniques use observation, interviews, and documentation. The data validity technique uses source triangulation and triangulation techniques. Data analysis techniques use data reduction, data presentation and conclusion drawn. The results of the study show that the application of loose part media to improve the numeracy development of children aged 5-6 years in kindergarten has been carried out through learning activities. Factors that support the application of loosepart media to improve children's numeracy development include natural factors, cognitive development factors, social background factors, learning motivation factors, teacher development factors, facilities and infrastructure factors, while the factors that hinder are environmental factors and teacher development factors.